Age-related impairments and influence of visual feedback when learning to stand with unexpected sensorimotor delays - Rasman, Brandon G.; van der Zalm, Christian; Forbes, Patrick A. (Frontiers in Aging Neuroscience, 2023)
Background: While standing upright, the brain must accurately accommodate for delays between sensory feedback and self-generated motor commands. Natural aging may limit adaptation to sensorimotor delays due to age-related decline in sensory acuity, neuromuscular capacity and cognitive function. This study examined balance learning in young and older adults as they stood with robot-induced sensorimotor delays. Methods: A cohort of community dwelling young (20 – 28 years, N = 20) and older adults (66 – 78 years, N = 20) participated in this balance learning study. Participants stood on a robotic balance simulator which was used to artificially impose a 250 ms delay into their control of standing. Young and older adults practiced to balance with the imposed delay either with or without visual feedback (i.e., eyes open or closed), resulting in four training groups. We assessed their balance behavior and performance (i.e., variability in postural sway and ability to maintain upright posture) before, during and after training. We further evaluated whether training benefits gained in one visual condition transferred to the untrained condition. Results: All participants, regardless of age or visual training condition, improved their balance performance through training to stand with the imposed delay. Compared to young adults, however, older adults had larger postural oscillations at all stages of the experiments, exhibited less relative learning to balance with the delay and had slower rates of balance improvement. Visual feedback did not influence relative learning magnitudes or learning rates for either age group. For all groups, balance improvements gained from training in one visual condition transferred to the untrained visual condition. Conclusion: Our study reveals that while advanced age partially impairs balance learning, the older nervous system maintains the ability to recalibrate motor control to stand with initially destabilizing sensorimotor delays under differing visual feedback conditions.